Estimation of local transmissibility in the early phase of monkeypox epidemic in 2022. (December 2022) - Kwok, Kin On; Wei, Wan In; Tang, Arthur; Wong, Samuel Yeung Shan; Tang, Julian W.
Abstract: Objectives: To estimate the basic reproductive number (Ro) to help us understand and control the spread of monkeypox in immunologically naive populations. Methods: Using three highest incidence populations including England, Portugal, and Spain as examples as of 18 June 2022, we employed the branching process with a Poisson likelihood and gamma-distributed serial interval to fit daily reported case data of monkeypox to estimate Ro. Sensitivity analyses were performed by varying mean serial interval from 6.8 to 12.8 days. Results: The median posterior estimates of Ro for monkeypox in the three study populations were statistically >1 (England: Ro = 1.60 [95% (credible interval) CrI, 1.50–1.70]; Portugal: Ro = 1.40 [95% CrI, 1.20–1.60]; Spain: Ro = 1.80 [95% CrI, 1.70–2.00]). Ro estimates varied over 1.30 to 2.10, depending on the serial interval. Discussion: The updated Ro estimates across different populations will inform policy makers' plans for public health control measures. Currently, monkeypox has a sustainable outbreak potential and may challenge healthcare systems, mainly due to declines in the population level immunity to Orthopoxviruses since the cessation of routine smallpox vaccination. Smallpox vaccination has been shown to be effective in protecting (≤85% effectiveness) against monkeypox infection in earlier times. So early postexposure vaccination is currently being offered in an attempt to control its spread.